Dressing Modern Frenchwomen Marketing Haute Couture, 1919-1939 - Stewart, Mary Lynn (Johns Hopkins University Press, 2008)
At a glance, high fashion and feminism seem unlikely partners. Between the First and Second World Wars, however, these forces combined femininity and modernity to create the new, modern French woman. In this engaging study, Mary Lynn Stewart reveals the fashion industry as an integral part of women's transition into modernity. Analyzing what female columnists in fashion magazines and popular women novelists wrote about the "new silhouette," Stewart shows how bourgeois women feminized the more severe, masculine images that elite designers promoted to create a hybrid form of modern that both emancipated women and celebrated their femininity. She delves into the intricacies of marketing the new clothes and the new image to middle-class women and examines the nuts and bolts of a changing industry-including textile production, relationships between suppliers and department stores, and privacy and intellectual property issues surrounding ready-to-wear couture designs. Dressing Modern Frenchwomen draws from thousands of magazine covers, advertisements, fashion columns, and features to uncover and untangle the fascinating relationships among the fashion industry, the development of modern marketing techniques, and the evolution of the modern woman as active, mobile, and liberated.